Intellectual entertainments : eight dialogues on mind, consciousness and thought - Hacker, P. M. S. (Peter Michael Stephan) (Anthem Press, 2019)
'Intellectual Entertainments' consists of eight dialogues on the nature of the mind and consciousness, thought and thinking, perceptual qualities and ownership of pain. Each dialogue has five participants, some living, some dead and some imaginary who represent different points of view. No philosophical knowledge is presupposed.
Keywords: Philosophical anthropology.; Philosophy of mind.; Thought and thinking.; Thinking; Anthropologie philosophique.; Philosophie de l'esprit.; Pensée.; philosophical anthropology.; thinking.; PHILOSOPHY -- General.; Philosophical anthropology; Philosophy of mind; Thought and thinking